Sacrifice ratios with long-lived effects - Lawrence Huiyan Zhang (The Johns Hopkins University, Department of Economics, 2001)
This paper contains a theoretical and empirical study of sacrifice ratios with long-lived effects including possible strong persistence effects or even hysteresis effects The empirical analysis is based on G-7 quarterly output data as well as unemployment data from 1960 to 1999 In this paper I develop some new methods to measure sacrifice ratios with long-lived effects I reach four conclusions: First sacrifice ratios with long-lived effects are larger than sacrifice ratios that do not account for long-lived effects Second from a theoretical model and simulation the standard method of measuring sacrifice ratios by Ball (1994) has a larger downward bias for countries with larger long-lived effects Third both random and fixed effect models show that there is a negative relationship between sacrifice ratios and initial inflations which can provide one explanation of the large magnitude of sacrifice ratios with long-lived effects in the 1990s compared with other periods Fourth there is no significant negative relationship between sacrifice ratios with long-lived effects and nominal wage rigidities.
Keywords: E52; E58; 330; Sacrifice Ratio; Long-Lived Effect; Persistence; Hysteresis; Disinflation Monetary Policy; Inflationsbekämpfung; Wirtschaftliche Anpassung; Anpassungskosten; Schätzung; G-7-Staaten